Biology modules with pogil approach to enhance students analytical thinking ability - I Rosadi; Maridi Maridi; W Sunarno (Pascasarjana Universitas Pendidikan Indonesia, 2018)
POGIL (Process Oriented Guided Inquiry Learning) approach for learning is important to be developed for high school since it can enhance students analytical thinking ability. This research aimed to determine feasibility and effectivity biology module with a POGIL approach to increase student analytical thinking ability. The module development was done by generates purposes, raises questions, uses information, utilizes concepts, makes inferences, makes assumptions, generates implications dan embodies a point of view. Data collection was questionnaire and test performed pretest and posttest with control group design. Two classes were selected randomly as samples consist of 30 students in each group. Descriptive data analysis was used to analyze the module feasibility and t-test was used to analyze the analytical thinking ability. The results showed that the feasibility of the module development has very good results based on an assessment of the experts, practitioners, and peers. Based on the t-test results, there is a significant difference between control class and experiment class (0.001), n-gain score of control and experiment class respectively 0.50 (medium) and 0.60 (medium). It shows that the module is more effective than the textbook. It is able to improve students analytical thinking ability and worthy to used in learning.